A higher loyalty truth, lies, and leadership - Comey, James (London Macmillan, 2018)
n his book, former FBI director James Comey shares his never-before-told experiences from some of the highest-stakes situations of his career in the past two decades of American government, exploring what good, ethical leadership looks like, and how it drives sound decisions. His journey provides an unprecedented entry into the corridors of power, and a remarkable lesson in what makes an effective leader.
Includes index
Keywords: Comey, James B., Jr., 1960-; United States. Federal Bureau of Investigation -- United States. -- Federal Bureau of Investigation; Leadership -- United States; United States -- Politics and government